2012
DOI: 10.1371/journal.pone.0038298
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide MicroRNA Expression Analysis of Clear Cell Renal Cell Carcinoma by Next Generation Deep Sequencing

Abstract: MicroRNAs (miRNAs), non-coding RNAs regulating gene expression, are frequently aberrantly expressed in human cancers. Next-generation deep sequencing technology enables genome-wide expression profiling of known miRNAs and discovery of novel miRNAs at unprecedented quantitative and qualitative accuracy. Deep sequencing was performed on 11 fresh frozen clear cell renal cell carcinoma (ccRCC) and adjacent non-tumoral renal cortex (NRC) pairs, 11 additional frozen ccRCC tissues, and 2 ccRCC cell lines (n = 35). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 38 publications
9
91
0
1
Order By: Relevance
“…Of note, more mi RNAs were downregulated or silenced in renal tumours than in normal tissue, and this downregulation or silencing [Au: OK?] was often associated with promoter methylation or copy number changes 179,[182][183][184][185][186][187][188] . Many of these mi RNAs target components of networks that are dysregulated by mutations or promoter methylation.…”
Section: Bap1mentioning
confidence: 99%
“…Of note, more mi RNAs were downregulated or silenced in renal tumours than in normal tissue, and this downregulation or silencing [Au: OK?] was often associated with promoter methylation or copy number changes 179,[182][183][184][185][186][187][188] . Many of these mi RNAs target components of networks that are dysregulated by mutations or promoter methylation.…”
Section: Bap1mentioning
confidence: 99%
“…Recently numerous studies have shown aberrant expression of microRNA-122-5p (miR-122) in human cancer tissues, including RCC (Zhou et al, 2010;Heinzelmann et al, 2011;Osanto et al, 2012), suggesting that it is a candidate tumor activator in RCC. miR-122 is one of the most frequent miRNA isolated in the liver and plays important roles in many aspects of liver physiology, such as stress response (Bhattacharyya et al, 2006) and lipid metabolism (Esau et al, 2006).…”
Section: Microrna-122 Promotes Proliferation Invasion and Migrationmentioning
confidence: 99%
“…However, the function and clinical significance of miR-125a-5p in RCC has yet to be explored (15). To determine whether miR-125a-5p is important for the tumorigenesis of RCC, human renal cancer and paired normal tissues were collected and compared for miR-125a-5p expression levels, using quantitative polymerase chain reaction (qPCR).…”
Section: Introductionmentioning
confidence: 99%